A Regional Comparison of Production-Based and Consumption-Based PM2.5 Emissions between China and Korea - Jiang, Min; Kim, Euijune (Journal of Environmental Policy and Administration, 2022)
There has been an increasing focus on the high levels of PM2.5 emissions and theworsening air quality in Korea and China. Recently, the debate over air pollution mitigationstrategies has shifted from implementing conventional “end-of-pipe” solutions focusing insteadon the direct role played by consumers. Central governments should distinguish different regions’respective pollution burdens to meet national emission reduction targets by considering theireconomic differences and industry structures. With the use of a multiregional input–outputanalysis approach, this paper breaks down the PM2.5 emission patterns of 19 different industriesin 9 Chinese regions and 16 Korean regions through a comparison of a production-basedaccounting (PBA) approach and a consumption-based emission accounting (CBA) approach. Byconstructing an inter-regional PM2.5 emission transfer matrix, this paper offers a more accurateanalysis of the allocation of emission reduction responsibility amongst the various regions. Themain finding was that there were significant differences in PM2.5 emissions between the regionsand industries in China and Korea; and when calculating the regional responsibility for PM2.5emissions, CBA was the more appropriate method for Korea; while for China, the choice of usingeither the PBA or CBA approach depended on the specific region. KCI Citation Count: 0